Safety of Zilver PTX Drug-Eluting Stent Implantation Following Drug-Coated Balloon Dilation in a Healthy Swine Model. (February 2018) - Torii, Sho; Yahagi, Kazuyuki; Mori, Hiroyoshi; Harari, Emanuel; Romero, Maria E.; Kolodgie, Frank D.; Young, Brandt; Ragheb, Anthony; Virmani, Renu; Finn, Aloke V.
Purpose: To compare the safety of Zilver PTX drug-eluting stents (DES) following drug-coated balloon (DCB) angioplasty or conventional balloon angioplasty (BA) in a healthy porcine iliofemoral artery model.Methods: DES implantation following DCB (DCB+DES) or BA (BA+DES) was assessed by angiography and histology in the nondiseased iliofemoral arteries of 20 animals, with sacrifice at 1, 3, and 6 months. Safety assessment compared quantitative measures of vessel integrity (eg, preservation of artery geometry, structure, and lumen dimensions; absence of aneurysm; malapposition) and histological parameters (eg, excessive inflammation). The percentage of uncovered struts could not be >30% per section and the endothelial cell loss had to be <50%. The vascular and skeletal muscle changes in the downstream regions were also assessed histologically for evidence of emboli.Results: No significant differences in safety parameters, including inflammation and endothelial cell loss, were observed between the 2 groups at all time points. Percentage of fibrin was significantly higher in DCB+DES at 3 months [20.0% (IQR 11.6, 28.4) vs BA+DES 4.2% (IQR 1.4, 9.6), respectively; p=0.04], with consistent trends between groups at all time points. Medial smooth muscle cell loss peaked at 1 month and was not statistically different between groups at any time point, although the loss was greater in the DCB+DES group. Sections with arterioles exhibiting paclitaxel-associated fibrinoid necrosis in downstream tissues were observed exclusively in the DCB group at 1 month (14.3% of sections) and 3 months (11.5%).Conclusion: This preclinical study suggests that Zilver PTX stent implantation is a safe strategy after DCB angioplasty and might be considered for patients who require stenting after DCB treatment.